O primeiro jardim da infância no Brasil:Emilia Ericksen - ., (2006)
This research has the objective of investigating the First kindergarten in Brazil, established by Emília Erichsen in 1862. Up to the present moment, the information that was found in the History of Education books and in the academic production was that the first kindergarten would have been established by Gabriel Gives in 1896 .Emília Ericksen sets her kindergarten in Castro, in the Province of Paraná based on the methodology of the German Pedagogue Friederich Froebel. Throughout this research it was tried to understand the meaning of infancy from ARIÈS, KUHLMANN, Jr and COSTA. The research is organized in three chapters. The first one has the objective of understanding the infancy concept, based on philosophical writings, related to this subject, in bibliographies on the subject, because it was understood that when analyzing the first kindergarten it would be important to clarify how the concept of infancy was put through time. The changes that occurred in this historical process, so that the child came to be considered a social being, were also searched in the first chapter. In the second chapter, the educator Friedrich Fröebel is pointed, together with the relevant aspects of his life and his contributions to the infantile education. Emília Ericksen's life is also pointed out. In the third chapter, the contributions of Emília Ericksen and the foundation of the First kindergarten in Brazil, which was established in Castro Pr in 1862, is stood out. In the third chapter the methodology used by Froebel in his Kindergartens is also studied. This kind of methodology was also the one adopted by Emília Ericksen in her kindergarten. The sources of this research were collected in the following institutions: Paraná Public Archives (in Curitiba - PR), House of Memory in Ponta Grossa, House of Memory in Castro, Campos Gerais Museum in Ponta Grossa, Sector of Documentation of the Secretariat of Education of the State of the Paraná and libraries of UNICAMP and UEPG. The developing of the research also had the participation of Emilia Ericksen's great-great-granddaughter, Estela Sandrini. The present dissertation demonstrates that its contribution lies in identifying the first kindergarten in Brazil and also the methodology developed to the Infantile Education in the XIX century.